Fungal pathogen and ethanol affect host selection and colonization success in ambrosia beetles. (1st August 2019) - Rassati, Davide; Contarini, Mario; Ranger, Christopher M.; Cavaletto, Giacomo; Rossini, Luca; Speranza, Stefano; Faccoli, Massimo; Marini, Lorenzo
Abstract: Ambrosia beetles exhibit broad host ranges but a narrow preference based on the condition of the host. Tissues infected by pathogens or containing ethanol can facilitate attacks by ambrosia beetles, although it still remains unclear how these factors interact. The present study aimed to examine how (i) chestnut logs infected with the fungal pathogen Cryphonectria parasitica and treated with ethanol (i.e. baited with ethanol lure, soaked in ethanol or untreated) and (ii) hornbeam logs soaked in different ethanol concentrations (3–12.5%) affect host selection and colonization success of ambrosia beetles. Ethanol‐soaked logs were more attractive to Anisandrus dispar than ethanol‐baited logs or untreated logs, although this difference was more evident in uninfected than infected logs. Increasing ethanol concentration in host tissues was differentially attractive to Xyleborinus saxesenii and Xylosandrus germanus . A nonlinear relationship was also documented between ethanol concentration and emergence of X. germanus adults. Overall, the results obtained suggest that the presence of C. parasitica in chestnut logs can affect host selection in ambrosia beetles. In addition, the ethanol concentration in tree tissues affects host selection and colonization success, although the effect varies depending on the beetle species. This contrasting response could be a niche‐partitioning mechanism based on ethanol within host tissues.